Aplikasi Sistem Informasi Administrasi Pada PD. Meteor Motor - Alexander Christofer Liem; Lily Puspa Dewi; Silvia Rostianingsih (Jurnal Infra, 2015)
PD. Meteor Motor is a company specialized in the sale of Honda motorcycles. The stock of the company has been run in a computerized, but other business processes (purchases and sales) run manually. The purpose of this thesis is to develop a web-based information system that is accessible by company management in operational activities. The application interface is designed using CSS and HTML. This information system is built by using PHP, Java, and HTML programming language. As for data storage uses MySQL. The results based on questionnaires on the application of information systems at PT. Meteor Motor, several conclusions can be drawn that 80% of respondents said that the design of the application system is quite easy to use, and as many as 20% of respondents said that the design of the application is easy to use, in addition as much as 60% of respondents said application system sufficient to meet the company's business processes, and as many as 40% of respondents said application system meets the company's business processes, as well as 60% of respondents said application system is easily accessible, and 40% of respondents said application system is very easily accessible